2015
DOI: 10.1007/s10554-015-0675-1
|View full text |Cite
|
Sign up to set email alerts
|

Relation between left atrial wall composition by late gadolinium enhancement and complex fractionated atrial electrograms in patients with persistent atrial fibrillation: influence of non-fibrotic substrate in the left atrium

Abstract: The complex fractioned atrial electrogram (CFAE) has been considered as the catheter ablation target of left atrium (LA) under persistent atrial fibrillation (PeAF). We evaluated the relation between the LA wall composition by late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) and the CFAE in patients with PeAF. Forty-three patients underwent LGE-CMR and CFAE mapping before catheter ablation for PeAF. The LA wall substrates were classified into three: the fibrotic, intermediate, and normal substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Multivariable analysis showed that LA LGE in the LIPV antrum, two or more segments of the LA with LGE, and LAV more than 112 mL were independently associated with PAF. The spatial resolution of LGE MRI, with its thin section thickness of 1-2 mm, allows noninvasive evaluation of LA wall tissue characteristics (20,21). The assessment of ablation-induced LA wall injury by using LGE MRI is possible because of the wall thickening as well as the contrast enhancement (22).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable analysis showed that LA LGE in the LIPV antrum, two or more segments of the LA with LGE, and LAV more than 112 mL were independently associated with PAF. The spatial resolution of LGE MRI, with its thin section thickness of 1-2 mm, allows noninvasive evaluation of LA wall tissue characteristics (20,21). The assessment of ablation-induced LA wall injury by using LGE MRI is possible because of the wall thickening as well as the contrast enhancement (22).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, ECG-gating CMR imaging during an arrhythmic attack may increase the image acquisition time and lead to adverse effects on the image quality (20). Third, CMR imaging allows the comprehensive evaluation of cardiac hemodynamics and tissue characteristics to enhance the understanding of AF (6,21). As CMR techniques advance, CMR imaging has been widely accepted as the effective pre-procedural imaging tool in the electroanatomic mapping of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the AF arrhythmogenic substrates are in various heart structures such as the superior vena cava (SVC), inferior vena cava (IVC), coronary sinus (CS), pulmonary vein (PV), left atrium (LA), left atrial appendage (LAA), and right atrium (RA). Therefore, in the management of AF by a catheter ablation, suitable targets include the LA, LAA, RA and adjacent vessel structures (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…All cardiac MR LGE images were analyzed independently by two experienced radiologists (blinded to the patients’ clinical and electrophysiological data) at a commercial software workstation (Terarecon iNtuition; TeraRecon, Foster City, CA, USA). The 3D reconstruction process used to produce MR LGE images was as previously described [ 8 , 9 ]. On transverse or coronal MR LGE images, epicardial and endocardial borders of LA walls were semi-automatically contoured to select the entire LA walls and reconstruct 3D LA models.…”
Section: Methodsmentioning
confidence: 99%